Question Number 1483 by Rasheed Ahmad last updated on 13/Aug/15

Prove that:  a+(b+c)+d=(a+c)+(d+b)

Commented byprakash jain last updated on 13/Aug/15

Basic properties of + operator. Or is it  something else?

Commented byRasheed Ahmad last updated on 14/Aug/15

Of course  basic properties.

Answered by Rasheed Soomro last updated on 16/Aug/15

LHS: a+(b+c)+d         =a+(c+b)+d     [ Commutative w. r. t +]         ={a+(c+b)}+d         ={(a+c)+b}+d   [Associative wrt +  ]         =(a+c)+{b+d}   [                 ∽                    ]         =(a+c)+(d+b)    [ Commutative wrt +]         =RHS

Commented by123456 last updated on 16/Aug/15

good :)